Five new species of Myrsidea Waterston (Phthiraptera: Menoponidae) from antshrikes and antbirds (Passeriformes: Thamnophilidae) - Price, Roger D.; Johnson, Kevin P.; Dalgleish, Robert C. (Zootaxa, 2008)
Five new species of Myrsidea parasitic on members of the avian family Thamnophilidae are described herein. They and their type hosts are Myrsidea klickai ex the Northern Slaty Antshrike, Thamnophilus punctatus (Shaw, 1809), M. dacostai ex the Barred Antshrike, Thamnophilus doliatus (Linnaeus, 1764), M. spellmani ex the Spotted Antbird, Hylophylax naevioides (Lafresnaye, 1847), M. milleri ex the Rufous-throated Antbird, Gymnopithys rufigula (Boddaert, 1783), and M. mayermae ex the White-faced Antbird, Pithys albifrons (Linnaeus, 1766). A portion of the mitochondrial COI gene for some of these and other species of Myrsidea was sequenced to compare genetic divergences.